The minority body: a theory of disability - Barnes, Elizabeth (Studies in feminist philosophy, 2016)
Elizabeth Barnes argues compellingly that disability is primarily a social phenomenon- a way of being a minority, a way of facing social oppression, but not a way of being inherently or intrinsically worse off. This is how disability is understood in the Disability Rights and Disability Pride movements; but there is a massive disconnect with the way disability is typically viewed within analytic philosophy. The idea that disability is not inherently bad or sub-optimal is one that many philosophers treat with open skepticism, and sometimes even with scorn. The goal of this book is to articulate and defend a version of the view of disability that is common in the Disability Rights movement.